Analysis of Students' Science Process Skills in Project-Based Chemistry Learning Integrated with Education for Sustainable Development - Paristiowati, Maria; Moersilah, Moersilah; Stephanie, Mian Maria (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to analyze the profile of science process skills through the implementations of project-based learning integrated education for sustainable development on acid-base material. The aim of the project is to create a natural acid-base indicator that can determine the pH range of various solutions and the concentration of a solution using the titration method. This study uses a qualitative research method, the interpretive paradigm with the research subjects of XI IPA students in Jakarta totaling 29 people. Data collection techniques are carried out by class observation, reflective journals of student, interviews, and tests of science process skills. The results showed that science process skills arises during learning and were classified as very good with an average value of 86.99% according to observations and classified as good with an average value of 72.26% in the test of science process skills. Students apply the education for sustainable development (ESD) concept during the project by choosing safe solvents and conducting small-scale experiments to reduce the waste produced. The application of this project is expected to make students have the skills of a researcher by paying attention to sustainable development in every decision they make during learning.